2021
DOI: 10.1113/jp282179
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure of mice to 890 ppm atmospheric CO2 alters growth trajectories and elicits hyperactive behaviours in young adulthood

Abstract: Atmospheric carbon dioxide (CO2) levels are currently at 418 parts per million (ppm), and by 2100 may exceed 900 ppm. The biological effects of lifetime exposure to CO2 at these levels is unknown. Previously we have shown that mouse lung function is altered by long‐term exposure to 890 ppm CO2. Here, we assess the broader systemic physiological responses to this exposure. Mice were exposed to either 460 or 890 ppm from preconception to 3 months of age, and assessed for effects on developmental, renal and osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Surprisingly, no pathological changes were observed in kidney structure at adulthood following exposure to the high CO 2 environment for 3 months (i.e. from gestation to young adulthood) or using measures of renal function (Wyrwoll et al 2022). Nor were differences in bone structural density identified, as would be expected if substantial physiological compensation was occurring.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Surprisingly, no pathological changes were observed in kidney structure at adulthood following exposure to the high CO 2 environment for 3 months (i.e. from gestation to young adulthood) or using measures of renal function (Wyrwoll et al 2022). Nor were differences in bone structural density identified, as would be expected if substantial physiological compensation was occurring.…”
mentioning
confidence: 87%
“…Further exploration is needed to determine how elevated CO 2 may affect pregnancy, ageing and the mechanisms underlying behavioural change. It is unclear from the study by Wyrwoll et al (2022) whether the reported hyperactivity is a result of changes in brain structure and function. Elucidating both behaviours and their neurological basis in this paradigm will not be trivial.…”
mentioning
confidence: 99%
See 3 more Smart Citations